STANDARD OF ORTHODONTIC ASSISTANCE FOR CLASS III ANGLE OBSTRUCTION PATHOLOGY ACCORDING TO CLINICAL CASE DESCRIPTION - Dmytrenko, M.I.; Smaglyuk, L.V.; Shevchyk, A.S.; Orlova, A.A. (World of Medicine and Biology, 2025)
Mesial occlusion due to mandibular hyperplasia and maxillary hypoplasia most significantly disrupts the aesthetic parameters of the face, reduces chewing efficiency, and disrupts the function of the temporomandibular joint. We present a standard of orthodontic care based on a description of a clinical case of a patient with mesial occlusion, taking into account individual age, clinical and anatomical features of the skull structure, as well as dental and bone age indicators and the stage of maturity of the palatal suture. The above example confirms the need for a comprehensive examination of orthodontic patients, which enables the objective determination of the morpho-functional state of the dento-maxillary area in cases of occlusion pathology and the development of a rational treatment plan for a particular patient.